2016
DOI: 10.1103/physrevc.93.045808
|View full text |Cite
|
Sign up to set email alerts
|

Model-independent determination of the astrophysicalSfactor in laser-induced fusion plasmas

Abstract: In this work, we present a new and general method for measuring the astrophysical S-factor of nuclear reactions in laser-induced plasmas and we apply it to 2 H(d,n) 3 He. The experiment was performed with the Texas Petawatt laser, which delivered 150-270 fs pulses of energy ranging from 90 to 180 J to D2 or CD4 molecular clusters. After removing the background noise, we used the measured time-of-flight data of energetic deuterium ions to obtain their energy distribution. We derive the S-factor using the measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…New methods to measure these quantities directly in the plasma have been recently investigated using a petawatt laser impinging on a cluster target. Fusion cross sections for d+ 3 He [16], dd [17] and the range [18] have been measured also in the cases where the system is prepared near the critical point for a liquid gas phase transition [19]. While the fusion cross sections have been found in reasonable agreement with accelerator experiments, the range showed some dependence on the cluster distribution, which in turn depends on the equation of state of the system [18,19].…”
mentioning
confidence: 78%
“…New methods to measure these quantities directly in the plasma have been recently investigated using a petawatt laser impinging on a cluster target. Fusion cross sections for d+ 3 He [16], dd [17] and the range [18] have been measured also in the cases where the system is prepared near the critical point for a liquid gas phase transition [19]. While the fusion cross sections have been found in reasonable agreement with accelerator experiments, the range showed some dependence on the cluster distribution, which in turn depends on the equation of state of the system [18,19].…”
mentioning
confidence: 78%
“…This scenario approximately describes secondary reactions and, in Coulomb explosion systems, beam-target reactions (as defined e.g. in [2,3]). It is then found that U = 0: an accurate evaluation of the average screened cross-section, via eq.…”
Section: Resultsmentioning
confidence: 99%
“…In the future, the model here discussed could be improved to include Debye-like screening and, possibly, to allow a comparison of its predictions with existing experimental data and simulations. For instance, [2] reports a reduction of the d + d cross-section extracted from Coulomb explosion measurements, with respect to conventional fixed-target experiments and Trojan Horse Method [7] measurements. The mechanism here described may be sufficient to explain that result, although further studies are needed to deduce the amount of net charge required to this end.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Coulomb explosion (CE) concept (see e.g. [2,3,4]), instead, the fuel is allowed through a nozzle to rapidly expand to average densities of ∼ 10 18 atoms/cm 3 [2] (to be compared with ICF hotspot densities, e.g. ∼ 10 25 atoms/cm 3 in the measurements in [13] at the NIF facility), forming molecular clusters.…”
Section: Non-neutral Laser-induced Plasmas For Fusion Energy Productionmentioning
confidence: 99%